Algunas reflexiones sobre por qué no se nombra la violencia sexual vivida por hombres - Guillermo Figueroa, Juan (2023)
In this text we propose possible reasons why the issue of sexual violence against male subjects is not so studied, named and addressed in research, public policies and campaigns to address and prevent the violence that they exercise and that they receive from others. We combine theoretical and semiotic reasons with political and ideological reasons. We discuss the lack of agency of those who receive violence, by not recognizing themselves as possible victims of said sexual assaults. We consider the religious and legal discourse, when reproducing imaginaries of sexual crimes and when defining victims and perpetrators. We reflect on consent, the border between an assault and an agreed sexual encounter and on emotional consequences in the person who lives the violence. Each of the reasons discussed suggests aspects of research, dialogue and collective reflection on interaction and sexual violence between people.